Belonging at Work: A Qualitative Meta-Synthesis of Workplace Inclusion, Social Identity, and Employee Well-Being - Maria Ulfah (Golden Ratio of Mapping Idea and Literature Format, 2026)
Organizations today face increasing pressure not only to enhance productivity and performance but also to create work environments where employees feel genuinely accepted, valued, and integrated as meaningful members of the organizational community. This systematic literature review adopts a qualitative meta-synthesis approach to analyze, synthesize, and integrate findings from prior research examining how belonging at work is formed through the interplay of workplace inclusion, social identity recognition, and employee well-being. Workplace belonging represents a critical organizational concern because it directly influences employee engagement, psychological health, work motivation, retention, and the quality of social relationships within organizations. Through a rigorous examination of peer-reviewed articles published between 2014 and 2026 across multiple academic databases, this study identifies several interconnected themes: workplace inclusion as a foundational condition, social identity recognition as a psychological mechanism, psychological safety as a mediating factor, inclusive leadership as a facilitating influence, social support and organizational culture as contextual moderators, and employee well-being as the ultimate outcome. The findings reveal that belonging at work is a multidimensional social-psychological phenomenon shaped by structural organizational practices, interpersonal relationships, leadership behaviors, and cultural norms. This review contributes theoretically by integrating previously fragmented literature into a comprehensive conceptual framework explaining the formation and consequences of workplace belonging. Practically, the findings offer actionable insights for organizational leaders and human resource practitioners seeking to design inclusive workplaces that promote employee health, engagement, and sustainable organizational performance.